The Impact of Using Tiktok on Student Lifestyles Case Study at Indonesian Education University Bandung Cibiru Campus - Neng, Hanum; Abidin, Yunus (PDPI (Perkumpulan Dosen Peneliti Indonesia), 2023)
The purpose of this study is to determine the impact of using the TikTok application on changes in student lifestyles. The development of the internet is increasingly advanced, triggering the emergence of various new social media, including TikTok. The tik tok application is an application in the form of videos, photos and live videos, and tiktok is an application that is liked and popular in almost all circles, especially students. With so many impacts that occur, from negative impacts to positive impacts. This study uses a mixture of quantitative and qualitative methods. Data collected by questionnaire technique, the respondents in this study were 10 students. The results of the study stated that the use of the Tik Tok application had positive and negative impacts on student lifestyles. The positive impact is being able to know the latest news, being able to sell and being a learning platform, the negative impact is being addicted, not knowing the time, and being lazy. The recommendation in this study is that managing time is good and important so that time is not wasted.